TRIAD: Whale Optimization Algorithm for 5G-IoT Resource Allocation Decision in Edge Computing - Lieira, Douglas Dias [UNESP]; Quessada, Matheus Sanches [UNESP]; Cristiani, Andre Luis; Immich, Roger; Meneguette, Rodolfo Ipolito (Institute of Electrical and Electronics Engineers (IEEE), 2021)
The massive growth in the number of 5G-IoT devices circulating in the world has increased the demand for computing resources in recent years. That way, it is necessary to search for the development of new solutions or improvements to existing ones. Edge computing is one of the solutions that have been used to improve the care of these types of devices. In this work, we proposed a mechanism that uses the whale optimization algorithm for 5G-IoT resource allocation decision in edge computing (TRIAD). The TRIAD was compared with the Greedy and Reliable techniques, available in the literature. The results show that the proposed algorithm had excellent efficiency in the service of the devices, in addition to denying fewer requests and blocking fewer devices during the search. The TRIAD, in some situations of the simulation, served approximately 265% more services, denied 56% less requests and blocked 65% less services.
TRIAD: Algoritmo de Otimização da Baleia para Decisão de Alocação de Recursos 5G-IoT em Computação de Borda
Keywords: edge computing; internet of things; meta-heuristic; resource allocation; whale optimization algorithm